The experience of risk in families: conceptualisations and implications for transformative consumer research - Pettigrew, Simone; Anderson, L.; Boland, W.; de La Ville, V.; Fifita, 'I.; Fosse-Gomez, M.; Kindt, M.; Luukkanen, L.; Martin, I.; Ozanne, L.; Pirouz, D.; Prothero, A.; et al. (Routledge, 2014)
Families represent an important context for understanding and addressing the various forms of risk experienced by consumers. This article defines and discusses the concept of risk as it applies to the familial unit, with a particular focus on the liminal transitions that occur within families and the resiliency required for families to identify and adopt effective coping strategies to manage these transitions. A framework is proposed that offers researchers an approach for applying concepts related to family risk to various consumption-related problems and issues. This framework constitutes a starting point that can be developed and expanded to facilitate a deeper understanding of the internal and external forces that influence families and their well-being, and the role consumption plays therein. Potential avenues for future transformative consumer research are proposed in this important but under-developed field.